Causes of Campus unrest as Perceived by Students of Kogi State Polytechnic, Lokoja - ADEDOKUN, Femi Johnson'; LAWAL, Abdulmumin Abubakar; ADEBAYO, Monsurat Folake; IBRAHIM, Muinat Abiodun'; SULYMAN, Kamaldeen Olohundare; OLOYIN, Abdulganiyu (International Journal of Educational Management, 2025)
This paper examined causes of campus unrest as perceived by students of Kogi State Polytechnic, Lokoja. The objectives of this paper was to investigate; (i) the most causes of campus crisis in Kogi State polytechnic, Lokoja. Descriptive research of survey type was adopted for the study. The population consisted of all 4,238 students in Kogi State polytechnic, Lokoja while the target population was the final year students. Three hundred and thirty six respondents were selected across the six schools in the polytechnic using simple random sampling technique. Self-designed questionnaire titled: "Causes of Campus Unrest as Perceived by Students Questionnaire (CCUPSQ) was used to collect necessary data from the respondents. One research question was raised and answered while three hypotheses were formulated and tested. Descriptive and Inferential statistics of mean ranking, t-test and Analysis of Variance (ANOVA) were used to answer the research questions and test hypotheses respectively at 0.05 level of significance. The findings of the study indicated that failure of authority to listen to students' complaints is the most causes of campus crisis in Kogi State polytechnic, Lokoja. The study concluded that inability of government to address some of the students grievances promotes students unrest irrespective of gender, study stage and residence status of students. Based on the findings of the study, therefore, it was recommended, among others that: the school authority should ensure there is adequate provision of fundamental infrastructure to enhance conducive teaching and learning in order to prevent student unrests.